Kepemimpinan Tuhan Yesus di Masa Krisis Sebagai Model Kepemimpinan Kristen Saat Ini - Sayang Tarigan; Yanto Paulus Hermanto; Nira Olivia P (STTI Harvest Semarang, 2021)
Abstract: Secular leadership is not the same as leadership inherited from the Lord Jesus. The leadership of Jesus is a historical and inspiring leadership model for every Christian leader from time to time. The superiority of Jesus' leadership model stems from the communication of the Father's vision to his followers with a touch of compassion which is the basis of His leadership.In this study the authors used qualitative methods. While the data collection process, the method approach used is literature study. Through a series of research conducted, there are various leadership models that are found, but the Christ leadership model provides superior characteristics and models, especially in times of crisis like today.Keywords: Leadership, Jesus, Christian.Abstrak: Kepemimpinan sekuler tidak sama dengan kepemimpinan yang diwariskan oleh Tuhan Yesus. Kepemimpinan Yesus di dunia merupakan model kepemimpinan yang bersejarah dan menginspirasi bagi setiap pemimpin Kristen dari zaman ke zaman. Keunggulan model kepemimpinan Yesus bertolak dari komunikasi visi Bapa kepada para pengikut dengan sentuhan belaskasihan yang menjadi dasar kepemimpinan-Nya. Dalam penelitian ini penulis menggunakan metode kualitatif. Sementara proses pengumpulan data, pendekatan metode yang digunakan adalah studi literatur. Melalui serangkaian penelitan yang dilakukan, terdapat beragam model kepemimpinan yang dijumpai, namun model kepemimpinan Kristus memberikan ciri dan model yang unggul, terutama dalam masa-masa krisis seperti saat ini.Kata kunci: Kepemimpinan, Yesus, Kristen.